Self-evaluation in patients treated for anorexia nervosa in Lublin province - Książek, Katarzyna; Grabska-Kusiak, Kinga; Słowińska, Agata; Dreher, Piotr; Mojsym-Korybska, Sylwia; Jurek, Anna Małgorzata (Journal of Education, Health and Sport, 2018)
Introduction. Self-esteem, or esteem, towards oneself has a tremendous impact on the various areas of human functioning. However, sometimes ICD-10 eating disorders with anorexia nervosa may adversely affect the perception of one's own body along with its self-evaluation. According to current medical knowledge, these disorders belong to serious mental disorders occurring mainly in young girls and women. Aim. The aim of the study was to determine the self-esteem of women treated for anorexia as classified by ICD-10 F 50.1. in medical facilities. Material and methods. The survey included 72 randomly selected women and adolescents of all ages who benefited from medical care and were diagnosed by specialists. The anonymous questionnaire was addressed to women and young girls suffering from anorexia nervosa. Patients were treated at the National Cancer Institute in Kraśnik, SN ZOZ in Lublin and USD in Lublin. The study was conducted from February to August 2017. Results. The study showed a significantly reduced self-esteem in patients, self-dissatisfaction, loss of sense of life. This disease mainly affects young girls and women up to 30 years of age who live in large cities. Conclusion. Positive was the result that 78% of women perceive anorexia as a disease and can properly indicate its adverse health consequences.